PROBLEMS OF PENETRATION OF LEXICAL UNITS INTO LANGUAGE - Khudoiberdieva Zarina Eshmirza kyzy (Galaxy International Interdisciplinary Research Journal, 2022)
The article discusses the factors that cause the appearance of borrowings in natural language, identifies the reasons for the spread of foreign words in the language system based on a clear differentiation of intra -linguistic and extra-linguistic factors.